Rethinking Climate Justice in the Digital Age: Pathways to Resilient Health Systems for Marginalized Communities - Jha, Ashima; Tolosa, James; Ramirez, Maria (International Journal of Nursing Information, 2025)
Climate change is not only an environmental challenge but a profound justice crisis, disproportionately affecting marginalized communities in low- and middle-income regions by intensifying social, economic, and health inequalities. In the digital age, rethinking climate justice requires integrating digital health innovations to strengthen health system resilience and equity. This study aims to reconceptualize climate justice in the digital age by examining the disproportionate health impacts of climate change on marginalized communities, evaluating the potential of digital innovations to strengthen resilient and equitable health systems, and proposing inclusive pathways that align digital transformation with human rights to safeguard vulnerable populations. The research employed a qualitative review and analytical approach, drawing on interdisciplinary literature from environmental sociology, climate policy, human rights law, and international development. It examined the intersection of environmental degradation, social exclusion, and health vulnerabilities, focusing on women, children, indigenous peoples, and ethnic minorities. Findings indicated that digital tools, including telemedicine and mobile health applications, enhanced healthcare access, system responsiveness, and equitable service delivery in climate-impacted regions. However, persistent barriers such as digital divides, weak infrastructure, and insufficiently inclusive governance limited their effectiveness. By bridging climate justice and digital health, the study offered actionable policy pathways and research directions to promote equitable health resilience amid escalating climate risks. These insights underscored the need for an integrated, rights-based, and intersectional framework that aligned digital transformation with climate justice, enabling inclusive policies and interventions that protected vulnerable populations and strengthened long-term health system adaptability.